2021
DOI: 10.1007/s11277-021-08932-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 crisis impact on the stability between parties in crowdfunding and crowdsourcing

Abstract: This research reviews challenges in building sustainable relationships between the parties involved in the crowdfunding and crowdsourcing projects, which are running in extreme situations, such as the COVID-19 pandemic. This study aims to solve problems that generate the crowdsourcing concerns and to find better alternatives to increase trust for crowdfunding among donors, as this impacts their strategic sustainability in the conditions of turbulence and COVID-induced financial crisis. It was found that factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Hence, this study fills the research gaps identified by scholars such as Wachira [11], Zribi [7], and Igra et al [19]. Further, although there are studies that examined the effects of the COVID-19 pandemic on crowdfunding performances [7,8,[19][20][21], these studies were confined to developed countries; hence, their findings do not necessarily yield similar results for Africa. Therefore, the current study responds to the limitations of these studies by focusing on Africa as a unit of analysis.…”
Section: Introductionmentioning
confidence: 78%
“…Hence, this study fills the research gaps identified by scholars such as Wachira [11], Zribi [7], and Igra et al [19]. Further, although there are studies that examined the effects of the COVID-19 pandemic on crowdfunding performances [7,8,[19][20][21], these studies were confined to developed countries; hence, their findings do not necessarily yield similar results for Africa. Therefore, the current study responds to the limitations of these studies by focusing on Africa as a unit of analysis.…”
Section: Introductionmentioning
confidence: 78%
“…Several studies have focused their attention on the analysis of access to finance in developing countries (Ayyagari et al, 2021;Nizaeva & Coskun, 2019;Manzoor et al, 2021) and alternative sources of finance during the pandemic (Sahay et al, 2020;Fu & Mishra, 2022;Liu et al, 2022). For several years technology was changing the landscape of the financial sector, increasing access to financial services (Sahay et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%